2012
DOI: 10.2147/imcrj.s35818
|View full text |Cite
|
Sign up to set email alerts
|

Collision tumors in the gastrointestinal tract: a rare case series

Abstract: A collision tumor is one where histology shows the presence of two distinct primaries involving the same organ without intermixture of individual cell types, ie, a side by side pattern. Here we present three rare cases of collision tumors involving the stomach and transverse colon. There were two cases of collision tumors involving the stomach, one of which was a combination of adenocarcinoma and low-grade non-Hodgkin’s (mucosa-associated lymphoid tissue) lymphoma, and the other showed the presence of non-Hodg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The vast majority of the cases (90%) in our review underwent gastrectomy (total or Given their rare nature, it is challenging to determine the behavior of CTs, but it is suggested that they have a greater risk for metastasis (42). Moreover, in adenocarcinoid CT, their progression seems to depend on the glandular component (9). Available data on their behavior are too limited to be able to reach safe conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…The vast majority of the cases (90%) in our review underwent gastrectomy (total or Given their rare nature, it is challenging to determine the behavior of CTs, but it is suggested that they have a greater risk for metastasis (42). Moreover, in adenocarcinoid CT, their progression seems to depend on the glandular component (9). Available data on their behavior are too limited to be able to reach safe conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Adenocarcinoma is the most common colonic malignancy but only presents with synchronous or metachronous tumors in 5% of cases. 5 , 6 In contrast, colorectal lymphoma is extremely infrequent, representing <0.5% of all primary CRC. 4 The clinical presentation of collision tumors is not specific and depends primarily on the affected organ.…”
Section: Discussionmentioning
confidence: 99%
“… 5 One hypothesis suggests that tumors arise in continuity through an accidental event and that the presence of one tumor precipitates the adjacent tumor by altering the microenvironment. 4 , 6 A lymphomatous process may be the initial event, compromising the patient’s immune system. 4 Nonetheless, there is no evidence that immunodeficiency induces activation of oncogenes or inactivation of tumor-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of neuroendocrine cells are often present inside gastric adenocarcinomas [ 28 ] while neuroendocrine carcinomas are often accompanied by gastric adenocarcinomas in other parts of gastrointestinal track [ 21 ]. It has been estimated that a neuroendocrine tumor can coexist with gastric adenocarcinoma in 0.4–4.3% of all cases [ 29 ]. Close association of these tumor types has created the concept of Mixed Endocrine Exocrine Carcinomas (MEECs) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%